Cognitive Behavioral Therapy for Depressed Adults with Mild Intellectual Disability: A Pilot Study - Hartley, Sigan L (J Ment Health Res Intellect Disabil, 2015)
BACKGROUND: There is a paucity of research on psychosocial treatments for depression in adults with intellectual disability (ID). In this pilot study, we explored the efficacy of a group CBT treatment that involved a caregiver component in adults with mild ID with a depressive disorder. METHOD: Sixteen adults with mild ID and a depressive disorder participated in a 10-week group CBT treatment and 8 adults with mild ID with a depressive disorder served as a treatment as usual (TAU) control group. Adults with mild ID and caregivers completed measures of depressive symptoms, behavior problems, and social skills at pre-treatment, post-treatment, and a 3-month follow-up. Adults with mild ID also completed a series of tasks to measure their understanding of the principles of cognitive therapy pre- and post-treatment. RESULTS: The CBT group demonstrated significant decreases in depressive symptoms and behavior problems from pre-treatment to post-treatment and these effects were maintained at a 3-month follow-up. The CBT group demonstrated significant improvements in their ability to infer emotions and thoughts based on various situation-thought-emotion pairings from pre-treatment to post-treatment. CONCLUSIONS: Findings indicate that adults with mild ID with a depressive disorder benefitted from a group CBT treatment with a caregiver component. Moreover, adults with mild ID appeared to benefit, at least in part, from the cognitive therapy components of the treatment, in addition to the behavior therapy components.